2022
DOI: 10.4251/wjgo.v14.i7.1307
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophile-to-lymphocyte, lymphocyte-to-monocyte, and platelet-to-lymphocyte ratios as prognostic and response biomarkers for resectable locally advanced gastric cancer

Abstract: BACKGROUND Perioperative fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT) improves prognosis in locally advanced gastric cancer (LAGC). Neutrophil-to-lymphocyte (NLR), lymphocyte-to-monocyte (LMR), and platelet-to-lymphocyte (PLR) ratios are prognostic biomarkers but not predictive factors. AIM To assess blood ratios’ (NLR, LMR and PLR) potential predictive response to FLOT and survival outcomes in resectable LAGC patients. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Based on previous research (Sturgeon et al 2010 ), the cutoff value of CEA and CA199 was 5 ng/ml and 37 U/ml, respectively. Besides, we calculated the prognostic nutritional index (PNI) and tumor-related inflammatory indicators, including neutrophil-to-lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), platelet to lymphocyte ratio (PLR) in accordance with previous literature (Tomás et al 2022 ; Pikuła et al 2022 ; Gao et al 2018 ; Liu et al 2017 ). Patients were divided into three groups respectively according to the number of positive tumor markers (CEA and CA199) before surgery and the number of incremental tumor markers after surgery.…”
Section: Methodsmentioning
confidence: 95%
“…Based on previous research (Sturgeon et al 2010 ), the cutoff value of CEA and CA199 was 5 ng/ml and 37 U/ml, respectively. Besides, we calculated the prognostic nutritional index (PNI) and tumor-related inflammatory indicators, including neutrophil-to-lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), platelet to lymphocyte ratio (PLR) in accordance with previous literature (Tomás et al 2022 ; Pikuła et al 2022 ; Gao et al 2018 ; Liu et al 2017 ). Patients were divided into three groups respectively according to the number of positive tumor markers (CEA and CA199) before surgery and the number of incremental tumor markers after surgery.…”
Section: Methodsmentioning
confidence: 95%
“…A 2021 Italian study with a cohort of locally advanced patients treated with neoadjuvant chemotherapy demonstrated that baseline high NLR is significantly correlated with worse OS and PFS ( 3 ). A 2022 study also investigated patients with locally advanced disease receiving preoperative chemotherapy, finding a significant association between higher values of NLR and decreased OS ( 68 ). These results are in concordance with our findings and suggest the utility of novel biomarkers to prognosticate survival across the landscape of GC scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we calculated the prognostic nutritional index (PNI) and tumor related in ammatory indicators, including neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), platelet to lymphocyte ratio (PLR) in accordance with previous literature. (Tomás TC et al 2022;Pikuła A et al 2022;Gao ZM et al 2018;Liu X et al 2017) Patients were divided into three groups respectively according to the number of positive tumor markers (CEA and CA199) before surgery and the number of incremental tumor markers after surgery. To further compare the predictive superiority between preoperative tumor markers levels and post-preoperative tumor markers increments, we divided patients into four groups based on whether preoperative tumor markers were positive and whether postoperative tumor markers were elevated.…”
Section: Data Collectionmentioning
confidence: 99%